Behavioral and Genomic Sensory Adaptations Underlying the Pest Activity of Drosophila suzukii. (15th February 2021) - Durkin, Sylvia M; Chakraborty, Mahul; Abrieux, Antoine; Lewald, Kyle M; Gadau, Alice; Svetec, Nicolas; Peng, Junhui; Kopyto, Miriam; Langer, Christopher B; Chiu, Joanna C; Emerson, J J; Zhao, Li
Abstract: Studying how novel phenotypes originate and evolve is fundamental to the field of evolutionary biology as it allows us to understand how organismal diversity is generated and maintained. However, determining the basis of novel phenotypes is challenging as it involves orchestrated changes at multiple biological levels. Here, we aim to overcome this challenge by using a comparative species framework combining behavioral, gene expression, and genomic analyses to understand the evolutionary novel egg-laying substrate-choice behavior of the invasive pest species Drosophila suzukii . First, we used egg-laying behavioral assays to understand the evolution of ripe fruit oviposition preference in D. suzukii compared with closely related species D. subpulchrella and D. biarmipes as well as D. melanogaster . We show that D. subpulchrella and D. biarmipes lay eggs on both ripe and rotten fruits, suggesting that the transition to ripe fruit preference was gradual. Second, using two-choice oviposition assays, we studied how D. suzukii, D. subpulchrella, D. biarmipes, and D. melanogaster differentially process key sensory cues distinguishing ripe from rotten fruit during egg-laying. We found that D. suzukii 's preference for ripe fruit is in part mediated through a species-specific preference for stiff substrates. Last, we sequenced and annotated a high-quality genome for D. subpulchrella. Using comparative genomic approaches, we identified candidate genes involved in D. suzukii 's ability to seek out and target ripe fruits. Our results provide detail to the stepwise evolution of pest activity in D. suzukii, indicating important cues used by this species when finding a host, and the molecular mechanisms potentially underlying their adaptation to a new ecological niche.